Distribution maps of marine algae from tite Iberian Peninsula and tite Balearie Islands. XI. Lobophora variegata (Lamour.) Womersley, Padinapavonica (L.) Lamour. andZonaria tournefortii (Lamour.) Mont. (Dictyotales, Fucophyceae) - Gómez Garreta, Amelia; Ribera, Mª Antonia; Barceló, María Carmen; Rull Lluch, Jordi (Botanica Complutensis, 1998)
HARCELÓ, M. C., GÓMEZ GARRETA, A., RIBERA, MA. & RIJLL LLIJCH, J. 1998. Distribution maps of marine algac from thc Iberian Peninsula and the Balearie Islands. XI. Lobophora variegala (Lamour.) Womersley, Padina pavonica (L.) Thivy y Zonaria tourne/<,rhi (Lamour.) Mont. (DictyotaLes, Fucophyceae). Bot. Coinpluteresis 22:179-186. Este trabajo ha sido subvencionado por la DGICYT con cargo al proyecto de investigación número PB 90-0461-COl-O 1. Botanica Con pluicnsie ISSN: 1)214-4565 [998, número 2?. [79-156 180 M.’ Corma Barceló ci al. We publish here the maps of the distribution along the Iberian Peninsula and the Halearic Islands of the genera Lobophora, Padina and Zonaría belonging to the Order Dictyotales. Each one of these genera are represented in this geograpéical area by only one species: Lobopliora variegata (Lamour.) Womersley, Padina pavonica (L.) Thivy y Zonaria tournejbrtii (Lamour.) Mont.